WOMEN'S LEADERSHIP COMMUNICATION STYLE WATER RESOURCES MANAGEMENT DEPARTMENT OF SOUTH SUMATRA PROVINCE - Canara Zikrillah Putra; Gita Astrid (Jurnal Prodi Ilmu Komunikasi, 2022)
ABSTRACT The purpose of this study was to identify communication styles of women in leadership positions in water resource management offices in South Sumatra. By using gender rectostyle theory in research. The method is qualitative and descriptive in nature, using data collection techniques in interviews, observations, and documentary research. The results of this study showed that communication styles in women's leadership in the PSDA South Sumatra provincial office were divided into structured communication styles, similarity-based communication styles, dynamic (aggressive) communication styles, and liberating communication styles. indicates that you are using Similarity-based communication styles will be the most common. Mainly used by female executives.